Asuhan Keperawatan Pada Klien Kanker Payudara Stadium Iiib Dengan Masalah Keperawatan Gangguan Integritas Kulit Di Ruang VI Rumah Sakit Umum Kabanjahe Tahun 2022 - Arianus Zebua; Herianto Bangun (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
The research design used is descriptive with a case study method. The study took 1 client with a medical diagnosis of breast cancer and problems with skin integrity disorders. Pre-survey data processing was taken in Room VI at Kabanjahe General Hospital. The research results showed that the client said there was a wound on the left breast, with objective data the color of the wound was blackish brown, there was blood mixed with a little pus, and when the bandage was removed the smell was unpleasant. After 3 days of nursing care, the wound can improve with the criteria of the wound being red, no tissue necrosis, no odor, no pus coming out and a little bleeding. The conclusion of the nursing care evaluation shows that the problem of impaired skin integrity is still in the partially resolved stage. Based on the results obtained, further research is still needed, because healing skin integrity disorders due to cancer takes quite a long time, so clients must be patient and comply with all ongoing treatment.